New look at performance appraisal for scientists and engineers - Wilson, Donald K.
Donald K. Wilson, Roland Mueser and Joseph A. Raelin call for complementing the traditional management-centered appraisal with a "professional development" appraisal.
A regenerated process would include periodic appraisal of the individuals's professional development, apart from evaluation of his or her corporate performance.
The performance appraisal as usually carried out by an organization's management is often incompatible with the needs of the technical staff. Nevertheless, it serves the organizational requirement for evaluation, albeit sometimes poorly. For most professionals, however, it probably does their development more harm than good. The authors propose two appraisals, a Management Performance Appraisal, and Professional Development Appraisal. The management performance appraisal can be utilized as a management tool conducted for traditional purposes. The professional development appraisal would be a collateral process, separated from the conventional appraisal, but used to enhance professional growth and facilitate the intergenerational transfer of professional culture. Its two main characteristics would be mastery of one's technical proficiency and development of one's inner-directed character. The professional development appraisal would be carried out typically by professional mentors rather than by management.
Keywords: Performance appraisal